Chylomicron retention disease in a 2-year-old girl with a novel deletion in the SAR1b gene: A case report and literature review - Ibrahim, Judy; Zaabi, Nuha Al; Hertecant, Jozef (Indian Journal of Child Health, 2018)
Chylomicron retention disease (CMRD) is a rare disorder of lipid absorption, and its prevalence is